Advances and Challenges in Entrepreneurship Education. (13th June 2013) - Vanevenhoven, Jeff; Vozikis, George; Solomon, George; Winkel, Doan
<x xml:space="preserve">Abstract</x> Recent global economic crisis has increasingly demanded bold action from organizations. If these organizations fail to respond appropriately, entrepreneurs will develop new meaningful solutions to the complex and dynamic needs of the market. Guidance of many of these future entrepreneurial leaders falls on the shoulders of those in higher education. My goal in this paper is to suggest a shift toward a more enacted approach in the delivery of this guidance. This suggestion represents my own interpretation, is not generalizable in all environments, and should therefore be viewed with caution.